PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 034 TELUK MEGA KECAMATAN TANAH PUTIH - Mizarni Mizarni; Munjiatun Munjiatun; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the students achievment of social studies SD Negeri 034 Teluk Mega fourth graderes still low with an average value of 62,00 and minimum completenness criteria (KKM) social studies is 70,00. Between students, amounting to 20 people only 8 students who achieve classical KKM with 40,00%. This research is Classroom Action Research (CAR), wich aims to improve the student achievement of social studies class fourth at SD Negeri 034 Teluk Mega Kecamatan Tanah Putih with implementation of model cooperative learning thype snowball throwing. Formulation of the problem: is the implementation of model cooperative learning thype snowball throwing can improve students achievment of social studies at SD Negeri 034 Teluk Mega fourth graderes?. The research was conducted on march 18, 2015 to april 11, 2015 by 2 cycles. Subjects were students of SD Negeri 034 Teluk Mega fourth graderes, totalling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. Activities of the teacher in the learning process in cycle I the first meeting to 57,50% and the second meeting improve to 70,00%. Cycle II first meeting and the second meeting improve 85,00% and the second meeting improve to 97,50%. Result of data analysis of students activities in the first meeting cycle I with the first meeting of an avarage of 57,50% and a second meeting improve to 65,00%. Cycle II first meeting improve 82,50% and the second meeting improve to 97,50%. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 62,00. In the first cycle improve an average of 71,75 with increase big as 15,73% and an impove in the second with an average of 82,50 with increase big as 33,06%. Result in the class fourth at SD Negeri 034 Teluk Mega that the implementation of model cooperative learning thype snowball throwing can improve students achievement of social studies at fourth graderes SD Negeri 034 Teluk Mega.Key Word: Cooperative Learning Thype Snowball Throwing, Students Achievement the